Faktor-Faktor Risiko Status Imunisasi Dasar Tidak Lengkap pada Anak (Studi di Wilayah Kerja Puskesmas II Kuala Tungkal) - Yundri Yundri; Mexitalia Setiawati; Suhartono Suhartono; Henry Setyawan; Kamilah Budhi (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2017)
Background : Basic immunization is a program conducted to protect the body from disease. Mother behavior, health care and environmental factor serve as a benchmark in the basic immunization status. This study aimed to analyze the risk factors of incomplete basic immunization in children.Methods : The research used observational analytic and cross sectional studynsupported by qualitative approach of in-depth interview method. The research population was all mothers with children aged 12 to 24 months with sample size of 92 respondents. Sampling method was conducted by purposive random sampling. Data collection was done by interviewing and the measuring instrument used is an questionaire. Data was analyzed by univariate, bivariate and multivariate.Results : Multivariate analysis showed poor maternal knowledge (p=0.0001) and lack of supportive attitudes of mothers toward immunization (p=0.0001), is a risk factor for incomplete basic immunization status in children. While mother's age, mother's education, mother's occupation, mother's perception of health facility condition, mother's perception on immunization staff role, number of child in the household and information media are not the risk factors of incomplete basic immunization status in children. A qualitative approach with in-depth interviews indicates that poor knowledge of immunization and the lack of supportive attitude of mothers toward immunization resulting in an incomplete basic immunization status.Conclusion : Risk factors for incomplete basic immunization status in children are poor mother's knowledge and lack of supportive attitudes of mothers toward immunization